Online brand, opportunities, realities and challenges for SMEs. Fresh recruits, a solution or new kind of orienteering challenge? - Happonen, Ari; Manninen, Laura; Santti, Ulla; Mariappan, Muralindran (International Journal of Engineering and Technology, 2021)
The research produced understanding how fresh employer’s private social media brand can be beneficial for a company brand. It was also found that the companies' own brand image was not inline with their set expectations for usage of employer social media brand and skills. For the given challenge, literary review on the means for improving the situation of financially limited SMEs was carried out. Overall research data is based on literature review and interview data with students and company executives. Based on interviews, companies are looking for applicants who have an "individual brand" with visible personality. In the interviews, companies perceived "brand" to be connected to distinguishable individuality and presence of a personality. The study objectivity is to stimulate discussion on SME brand structuring as well as impact of individual brands into the SME brand building efforts with practical action options. Individual brands should be taken into account in recruitment and special attention needs to be put to the following orientation process, social media usage and processes of brand construction, with the new recruits. Whether the company has guidelines for social media actions or not, the public presence of the employee connects their brand with the company online brand, both in good and bad. Clear strategies and objectives for (new) employees how to connect their individual brand to company brand building is needed to be given from companies to their employees. This will also require guidelines for behavior in social media for employees, when communicating trough social media profiles, which could be connected back to the employing organization. Lastly, we studied expectations and beliefs of young recruits and companies into the key factors at the recruitment process, revealing mis alignment between the students and companies’ views. Keywords: Brand; Digitalization; Employment; Individual brand; Organizational brand; Recruitment; Small and medium-sized enterprises; SME; Social media.